2011
DOI: 10.1021/es202110d
|View full text |Cite
|
Sign up to set email alerts
|

Role of Titanium Dioxide Nanoparticles in the Elevated Uptake and Retention of Cadmium and Zinc in Daphnia magna

Abstract: Titanium dioxide nanoparticles (nano-TiO(2)) are now widely applied in consumer products, and the dispersion of nano-TiO(2) may adsorb metals and modify their behavior and bioavailability in the aquatic environment. In the present study, the aqueous uptake, dietary assimilation efficiency (AE), and efflux rate constant (k(e)) of two toxic metals (cadmium-Cd, and zinc-Zn) adsorbed on nano-TiO(2) in a freshwater zooplankton Daphnia magna were quantified. The biokinetics was then compared to daphnids that were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(62 citation statements)
references
References 41 publications
3
59
0
Order By: Relevance
“…In addition, previous studies have pointed out the enrichment of heavy metals in muscle, gills, liver, and kidney of fish (Fazio et al, 2014;Svecevicius et al, 2014;Wei et al, 2014). The NPs enhance the uptake heavy metal and organic toxicants (Baun et al, 2008;Tan et al, 2012;Wang et al, 2012Wang et al, , 2014. The previous studies also reported the enhanced uptake of toxicants in the presence of NPs, can greatly affect the toxicity of potential environmental pollutants (e.g., heavy metal and organic toxicants) Wang et al, 2014).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, previous studies have pointed out the enrichment of heavy metals in muscle, gills, liver, and kidney of fish (Fazio et al, 2014;Svecevicius et al, 2014;Wei et al, 2014). The NPs enhance the uptake heavy metal and organic toxicants (Baun et al, 2008;Tan et al, 2012;Wang et al, 2012Wang et al, , 2014. The previous studies also reported the enhanced uptake of toxicants in the presence of NPs, can greatly affect the toxicity of potential environmental pollutants (e.g., heavy metal and organic toxicants) Wang et al, 2014).…”
Section: Discussionmentioning
confidence: 93%
“…For instance, a previous study focused on the bioconcentration of the e-waste (BDE-209) that can be absorbed by nano-TiO 2 . Several previous studies focused on the enhanced bioaccumulation of metals mixed with NPs in aquatic ecosystems Tan et al, 2012). Their results showed that the increasing concentration of Cadmium and Zinc is related to NPs adsorption in Daphnia magna experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that n-TiO 2 can adsorb heavy metals [4,34,44] or organic toxicants, including tributyltin, PBDEs, DDT and tetrachlorodibenzo-p-dioxin [TCDD] [12,13,45,46], while study showed the aggregation and subsequent sedimentation of nTiO 2 with tributyltin [12]. At the same time, we did not measure and (E) GSH content in larvae after exposure to PCP alone (0, 3, 10, and 30 g/L) and in the presence of n-TiO2 (0.1 mg/L) for 6 days.…”
Section: Discussionmentioning
confidence: 99%
“…Test n-TiO 2 solutions were prepared immediately prior to use by diluting the stock solutions with fresh charcoal-filtered water and sonicating (50 W/L, 40 kHz) for 20 min [34]. The test solution was renewed every 24 h with new n-TiO 2 to maintain relatively consistent levels of n-TiO 2 exposure.…”
Section: Preparation and Characterization Of N-tiomentioning
confidence: 99%
“…The sorption behavior of nano-TiO 2 includes physical sorption through electrostatic forces and chemical sorption through chemical bonding Yang et al, 2013). Several studies have reported that the uptake and retention of toxic metals in carp and Daphnia is enhanced when they are adsorbed on nano-TiO 2 (Tan et al, 2012;Zhang et al, 2007). Furthermore, toxicity at high concentrations of nano-TiO 2 (e.g.…”
Section: Introductionmentioning
confidence: 99%